2016
DOI: 10.1111/jopr.12499
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Failure of Endocrowns Manufactured with Different Ceramic Materials: An In Vitro Biomechanical Study

Abstract: Mechanical failure of endocrown restorations does not significantly differ for silica-based ceramics modified either with zirconia or polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 21 publications
2
38
1
5
Order By: Relevance
“…From the point of failure modes, while only repairable fractures were observed in resin-ceramic group, catastrophic failures, as much as 70%, were seen in the lithium disilicate group 17) . On the other hand, Aktaş et al 26) found that different CAD/CAM materials such as alumina silicate ceramic (Vita Mark II), zirconiareinforced glass ceramic (Vita Suprinity) and polymerinfiltrated ceramic (Vita Enamic) with different elasticity moduli have no statistically significant effect on the fracture strength of molar endocrowns. But, all the specimens in zirconium-reinforced lithium disilicate group showed catastrophic failures, also known as nonrepairable failures, whereas mostly repairable fractures were observed in the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the point of failure modes, while only repairable fractures were observed in resin-ceramic group, catastrophic failures, as much as 70%, were seen in the lithium disilicate group 17) . On the other hand, Aktaş et al 26) found that different CAD/CAM materials such as alumina silicate ceramic (Vita Mark II), zirconiareinforced glass ceramic (Vita Suprinity) and polymerinfiltrated ceramic (Vita Enamic) with different elasticity moduli have no statistically significant effect on the fracture strength of molar endocrowns. But, all the specimens in zirconium-reinforced lithium disilicate group showed catastrophic failures, also known as nonrepairable failures, whereas mostly repairable fractures were observed in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of the elasticity modulus of both materials and dentin play an important role on the failure behavior of the ceramics during the loading test 17,26) . The stresses observed in materials which have similar elasticity moduli with respect to dentin were spread, whereas rigid materials with higher elasticity moduli than dentin resulted in stress accumulation and catastrophic failures 17,26) . Catastrophic failures occurred only for the TZI material, which has higher elasticity moduli (210 GPa) than dentin (18.6 GPa) 43,44) (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the restoration of endodontically treated teeth, CAD/CAM advocates emphasize the “endocrown” method, which consists of a merged crown and core unit adhesively bonded into the pulp chamber and the remaining tooth structure . The endocrown method is said to provide a more conservative option to traditional post and core restorative strategies while providing equitable results . Dejak and Młotkowski using an in silico finite element analysis reported that under simulated masticatory function the endocrown had lower dentin stress concentration than compared to traditional post and core methods.…”
Section: Introductionmentioning
confidence: 99%